Implementasi Kurikulum Merdeka pada Pembelajaran PPKn untuk Meningkatkan Minat Belajar Peserta Didik Kelas XI di SMA Negeri 1 Padarincang - Budi, Agung Setia; Fujiah, Fujiah (COGNITIVISM: Journal of Educational Research and Development, 2025)
This study aims to find out the implementation of the independent curriculum in Civic Education learning to increase students' learning interest in class XI at SMA Negeri 1 Padarincang. The research method used is a qualitative method with data collection techniques through interviews, observations, and documentation. Data analysis is carried out through data reduction, data presentation, and drawing conclusions. The research results indicate that the implementation of the Independent Curriculum in Civic Education Learning can increase students' learning interest through active learning and a project-based approach, which prioritizes values of mutual cooperation, independence, and justice. The role of teachers as role models in demonstrating tolerance and fairness is also proven to be significant in motivating students. The challenges faced include limited facilities and limited time for implementation. Efforts to overcome these challenges include effective time management, the use of creative media, as well as personal and emotional approaches to students. In conclusion, the implementation of the Independent Curriculum, supported by the active role of teachers, can increase students' learning interest and shape positive student character.